The Biochemistry of bile acids and their HPLC-MS Analysis - Leibetseder, Felix (Jihočeská univerzita, 2018)
The aim of this thesis was to summarize the biological importance and the physico-chemical properties of bile acids, to investigate the current methods for detection and quantification and to develop a quick and reliable HPLC-MS method to detect bile acids in biological systems, such as urine and plasma.
The Biochemistry of bile acids and their HPLC-MS Analysis